Technology Acceptance Model on E-procurement toward Indonesia’s Procurement Governance - Suardi, Imelda (Publikasi Indonesia, 2026)
Electronic procurement (e-procurement) has been widely adopted as a public sector reform to improve procurement governance, particularly in developing countries. In Indonesia, e-procurement has been implemented nationally through the Layanan Pengadaan Secara Elektronik (LPSE); however, empirical evidence on its governance impact remains limited. This study examines the effect of e-procurement implementation on procurement governance in Indonesia’s government using the Technology Acceptance Model (TAM). E-procurement implementation is measured by perceived usefulness and perceived ease of use, while procurement governance is operationalized as a multidimensional construct encompassing transparency, accountability, efficiency, effectiveness, fairness, competitiveness, monitoring, capacity, and accessibility. Primary data were collected from Indonesian government officials involved in e-procurement implementation and analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The findings show that e-procurement implementation has a positive and significant effect on procurement governance, indicating that higher acceptance of the system contributes to improved governance quality. This study contributes to the literature by integrating technology acceptance theory with public procurement governance and provides empirical evidence from a developing-country context to inform policy and practice.